068. Revealing the Hidden Giant: When Giant Appendicitis Mimics A Mesenteric Cyst in Recurrent Sigmoid Volvulus – A Case Report - Wari, Deastri Anjeas; Mujiburrahman, Husnan; Setyawan, Nurcahya (JBN (Jurnal Bedah Nasional), 2024)
Background : Giant appendicitis is an exceptionally rare condition that can mimic other intra-abdominal pathologies, including mesenteric cysts, due to its unusual size and presentation. Distinguishing between these entities is chalenging due to its resemblances. Case : A 56-year-old woman with a history of chronic constipation who was admitted to the emergency department with abdominal distension and inability to defecate. Abdominal examination revealed a distended abdomen with visible bowel contour and an abdominal X-ray showed coffee bean appearance, suggestive of sigmoid volvulus. An exploratory laparotomy revealed twisting of the sigmoid colon. After reducing the volvulus and confirming viability of the sigmoid, a loop sigmoidostomy was performed to prevent recurrent volvulus. Intraoperatively, a mass resembling a mesenteric cyst was identified, which was subsequently confirmed to be a case of giant appendicitis. Conclusion: Considering giant appendicitis in the differential diagnosis of abdominal masses resembling mesenteric cysts is important, particularly in patients with chronic constipation and recurrent volvulus, to ensure timely and appropriate surgical management.